Surface Reconstruction of Ni‐Rich Layered Cathodes: In Situ Doping versus Ex Situ Doping. Issue 7 (1st May 2022) - Wang, Linzhe; Qin, Jian; Bai, Zhimin; Qian, Huaming; Cao, Yanyan; Sari, Hirbod Maleki Kheimeh; Xi, Yukun; Shan, Hui; Wang, Shuai; Zuo, Jiaxuan; Pu, Xiaohua; Li, Wenbin; et al.
Abstract : The structural instability and sluggish Li + diffusion kinetic of the nickel‐rich LiNi x Co y Mn1− x − y O2 (NCM) cathode still hinder its further commercialization for lithium‐ion batteries. Doping heteroatoms are widely studied as an effective strategy to maintain structural and thermal stability for improving the capacity retention of NCM during cycling. Herein this work, in situ Zn 2+ ‐doped NCM (in situ Zn‐NCM) is successfully designed by atomic layer deposition (ALD) combined with annealing. In comparison to ex situ Zn 2+ ‐doped NCM (ex situ Zn‐NCM), in situ Zn‐NCM can better enhance the layered structure stability and reduce the generation of surface defects due to that it has lower migration energy barrier and more uniform distribution of heteroatoms. As a result, at a high cutoff voltage of 4.5 V, in situ Zn‐NCM with the obvious advantages of lower cation mixing, better phase transition stability, as well as more efficient charge transfer displays higher reversible capacity (i.e., 203.2 mAh g −1 at 50 mA g −1 ) and initial Coulombic efficiency (85%) compared to ex situ Zn‐NCM and the pristine NCM. Therefore, in situ doping is a novel and universal strategy to enhance battery performance of high‐energy‐density NCM cathodes for lithium‐ion batteries. Abstract : The atomic layer deposition derived general strategy has been designed to achieve a precise surface reconstruction of in situ doping cathodes with stabilizing the interface. Originating from low migration energy barrier and uniform distribution of heteroatoms, in situ doping cathodes show the obvious advantages of low cation mixing, high phase transition stability as well as efficient charge transfer.